Sistem Pertahanan Rakyat Semesta Pasca Berlakunya UU PSDN Untuk Pertahanan Negara - SAHABUDDIN, ZAINAL ABIDIN; RAMDANI, EGGY ARMAND (Universitas 17 Agustus 1945 Surabaya, 2020)
Indonesia's defense system is clearly stated in the Constitution (UUD 1945), namely the The Total People's Defense and Security (Sistem Pertahanan Rakyat Semesta, Sishanta). Sishanta has a strong philosophical and historical basis in Indonesian culture. Sishanta's efficacy in dealing with threats has been proven in the nation's history. The enactment of the National Resource Management Act (PSDN) for National Defense on 26 September 2019 became a new chapter in reviving the concept of Sishanta under a strong legal umbrella. This study examines more deeply the Indonesian culture of defense, how to implement Sishanta after the ratification of the PSDN Law. The research method used is analytical descriptive. The results showed that the Sishanta was the ideal Indonesian defense system in the face of threats. One of Sishanta's implementing is